Experience of Paleotectodynamic Analysis of Rank Components of Mesozoic-Cenozoic Movements and Deformations Using the Example of the Central Part of Bukharo-Khiva Region - R. A. Umurzakov; H. A. Akhmedov (Геодинамика и тектонофизика)
The article describes the methodological basis and some first experience results of applying paleotectodynamic analysis of tectonic movements rank components and deformations to study the features of geological development of a certain territory of the Bukharo-Khiva region central part in the Mesozoic – Cenozoic. The relevance of the work is determined by the need to revise the traditional methods of historical and structural analysis, based on which the conditions of formation and age of oil and gas structural traps are determined to improve the reliability of prognostic works. Paleotectodynamic analysis, as a new direction of studying the geologic evolution history, provides an assessment of the duration of manifestation of tectodynamic systems (paleotectonic stresses, tectonic movements and deformations) of different ranks in geologic history, study of the paleotectonic development of rank components of tectonic movements and deformations in the intervals of tectodynamic system action, determination of the relative age of formation of structural elements, their inheritance, as well as determination of the relative age of formation of structural elements, their inheritance, role or contribution to the geological evolution.The main indicator, on the basis of which the possibility to identify an independent (integral) tectodynamic system is determined, is the stress field type and deformation regime. In the Mesozoic – Cenozoic of the western part of the Tien Shan, five phases of alternating change of tectonic stress fields of the first (for this region) rank and associated deformation regimes were identified. In the first approximation, they correspond to: Early – Middle Jurassic, Late Jurassic, Cretaceous, Paleogene, and Neogene-Quaternary time. On this basis, the paper substantiates the necessity to revise and modify the classical methods of historical-structural (paleotectonic) analysis, which should be performed for each rank component separately, taking into account the interaction of both peer-to-peer and multi-rank elements. In this approach, the most important indicator is the feedback sign between different rank elements of tectodynamic systems. On the example of the central part of the Bukharo-Khiva oil-and-gas-bearing region, paleotectonic maps-schemes of three ranks for the above-mentioned time intervals were obtained. The previously unknown features of the structural plans of different horizons and their evolution in the Mesozoic – Cenozoic history were established. They served as a basis for further traditional historical-structural analysis with the construction of isopachic triangles along the selected intervals for each rank component in order to assess the tectonic conditions and time of formation of anticlinal oil and gas traps.